Iterative CT reconstruction in abdominal low-dose CT used for hybrid SPECT-CT applications: effect on image quality, image noise, detectability, and reader's confidence. (June 2019) - Grosser, Oliver S; Ruf, Juri; Kupitz, Dennis; Czuczwara, Damian; Loewenthal, David; Thormann, Markus; Furth, Christian; Ricke, Jens; Denecke, Timm; Pech, Maciej; Kreissl, Michael C; Amthauer, Holger
Background: Iterative computed tomography (CT) image reconstruction shows high potential for the preservation of image quality in diagnostic CT while reducing patients' exposure; it has become available for low-dose CT (LD-CT) in high-end hybrid imaging systems (e.g. single-photon emission computed tomography [SPECT]-CT). Purpose: To examine the effect of an iterative CT reconstruction algorithm on image quality, image noise, detectability, and the reader's confidence for LD-CT data by a subjective assessment. Material and Methods: The LD-CT data were validated for 40 patients examined by an abdominal hybrid SPECT-CT (U = 120 kV, I = 40 mA, pitch = 1.375). LD-CT was reconstructed using either filtered back projection (FBP) or an iterative image reconstruction algorithm (Adaptive Statistical Iterative Reconstruction [ASIR]®) with different parameters (ASIR levels 50% and 100%). The data were validated by two independent blinded readers using a scoring system for image quality, image noise, detectability, and reader confidence, for a predefined set of 16 anatomic substructures. Results: The image quality was significantly improved by iterative reconstruction of the LD-CT data compared with FBP ( P ≤  0.0001). While detectability increased in only 2/16 structures ( P  ≤ 0.03), the reader's confidence increased significantly due to iterative reconstruction ( P  ≤ 0.002). Meanwhile, at the ASIR level of 100%, the detectability in bone structure was highly reduced ( P  = 0.003). Conclusion: An ASIR level of 50% represents a good compromise in abdominal LD-CT image reconstruction. The specific ASIR level improved image quality (reduced image noise) and reader confidence, while preserving detectability of bone structure.